TO STUDY COMPARISON OF EFFICACY OF NEBULIZED KETAMINE VERSUS LIGNOCAINE FOR POSTOPERATIVE SORETHROAT - Dr. Sonali Savarn; Dr. Sarthak Mishra; Dr. Rajbahadur Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background & Methods: The aim of the study is to compare efficacy of Nebulized ketamine versus lignocaine for postoperative sorethroat. Parameters monitored include postoperative sorethroat immediately after extubation, 2hrs, 4hrs, 8hrs, 12hrs and 24hrs. General anesthesia was given 10 minutes after nebulization. Standard monitors like blood pressure, ECG and SPO2 were monitored.Results: The severity of postoperative sorethroat was less in lignocaine and ketamine group compared to control group. On follow up for 24 hours, ketamine group provided relief for longer duration as compared to lignocaine group. Hemodynamic parameters were comparable in all three groups.Conclusion: Preoperative nebulized ketamine is helpful at reducing the occurrence and severity of postoperative sore throat without causing any adverse effects and also effective for longer duration as compared to lignocaine . This technique helps anaesthetist in management of the ‘little big problem’ of post-operative sore throat.